PENGARUH PEMBERIAN REWORD DAN PUNISHMENT TERHADAP PRESTASI BELAJAR IPS KELAS V SD NEGERI 1 BAADIA - Intan, Muh Nur (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2021)
The purpose of this study is to see how offering reward and punishment affects student progress in Indonesian Class V SD Negeri 1 Badiaa on the subject of ethnic and cultural diversity. The descriptive quantitative approach was utilized in this study, which is a research design that uses numbers and statistics to clearly and significantly explain research variables. If there is an influence in this classroom, action research is deemed to be successful. The participants in this study were 20 fifth-grade children from SD Negeri 1 Badiaa, with 12 males and 8 females. The obtained rxy of 0.81 was revealed in the results. If you pay carefully, you'll notice that the influence index score obtained is negative. This suggests that the X variable (Giving Reword and Punishment) has a considerable influence on the Y variable (Student Learning Achievement). When we look at the magnitude of the acquired rxy, which is 0.81, we see that it falls between 0.70 and 0.80. The effect between the variables X and Y is said to be strong or high when the coefficient is 0.90.